Springtime sea fog penetration in Qingdao: Anomalous moistening and diurnal cooling - Song, Shu-Tong; Shi, Xiao-Meng; Zhang, Su-Ping; Chen, Xian-Yao; Xue, Yun-Chuan; Zhao, Wei; Yang, Chao; Huang, Bin; Yi, Li (Frontiers in Earth Science, 2022)
Sea fog often penetrates adjacent coastal areas, a process called sea fog penetration (SFP). SFP can cause traffic accidents and other economic losses. Qingdao, an international port city with a dense population, suffers from SFP originated over the Yellow Sea in the boreal spring (March-May); the process, however, is not well studied. Based on hourly observations from buoys and automatic weather stations distributed in Qingdao and its adjacent islands, we composite SFP events to reveal their spatiotemporal features and to investigate mechanisms involved. Results show that these SFP events often penetrate inland areas from southeast to northwest and last 5-8 hours at night. We further use reanalysis data to reveal that during the daytime before SFP, strong moisture advection at 925-975 hPa brings sufficient water vapor from Yellow Sea to Qingdao; the water vapor then transfers downward to the surface via background descending motion and turbulent mixing. The daytime anomalous moistening, together with the following diurnal cooling at night, saturates the surface atmosphere and hence facilitates SFP. The strength of the SFP depends on the strength of daytime anomalous moistening. Considering the moistening leads SFP by about a day, we use this relationship to predict the intensity of SFP. The accuracy of predicting SFP events could reach 50%~80%, which highlights the predictability of intensity of SFP in Qingdao.